ANALISIS DAN PERANCANGAN BLUEPRINT INFRASTRUKTUR JARINGAN KOMPUTER UNTUK MENDUKUNG IMPLEMENTASI SISTEM INFORMASI PADA STMIK LOMBOK - Ahmad Tantoni; Arief Setyanto; Eko Pramono (Informasi Interaktif, 2018)
The research objectives of obtaining blueprint network infrastructure that supports information systems and construction of new campus buildings and compare network performance before and after the design of computer network infrastructure.Problems that occur in STMIK Lombok is wanting the design of new network infrastructure because in access the Internet or access the information system, the civitas campus feel slow access in using the network connection because the computer network infrastructure is not maximized, wants better/improved network performance so as not to interfere with the organization's business processes and implementing the previously researched information system can work as expected. Moreover, the statistical data on the number of students shows an increasing number of students from each academic year making the need for renewal of existing computer network infrastructure.The problem is not only that, related to the construction of new campus building, the computer network has to be redesigned to increase the scalability of campus civitas which increasingly increasing year and the management of STMIK Lombok wanting alignment between campus building construction by designing blueprint of computer network infrastructure. So needed an analysis and design of blueprint computer network infrastructure technology that is structured so that when implemented information system and building of STMIK Lombok building can run well. This research is intended to give solution in the form of blueprint design of computer network infrastructure that support pengimplentasian information system and construction of new campus building at STMIK Lombok.Keywords: Blueprint, Computer Network Infrastructure, Performance, Virtual LAN